Quality of life after rectal-preserving treatment of rectal cancer. Issue 11 (November 2020) - Jones, Helen J.S.; Al-Najami, Issam; Cunningham, Chris
Abstract: Aim: Rectal-preserving strategies for managing rectal cancer are becoming more common for selected groups of patients. Oncological outcomes are similar, so long as patients are closely followed, and any local recurrence detected and managed promptly. Functional outcomes are now of increasing importance so patients can be appropriately counselled prior to treatment. We examine functional outcomes in patients managed by multimodal organ-preservation approaches allowing comparison of the full range of strategies. Materials and methods: Patients attending for surveillance after any of four rectal-preserving treatments for rectal cancer (radiotherapy [RT], local excision [LE], RT then LE or LE then RT) were asked to complete a questionnaire assessing general quality of life and bowel, urinary and sexual function. Results: 100 patients completed questionnaires: 34 managed by neoadjuvant RT followed by 'watch and wait', 40 by LE, and 26 who had composite treatment (18 LE + RT and eight RT + LE). Questionnaires were completed a median of 10 months (IQ range 6–33) following treatment. The LE only group tended to have better bowel function, while the composite groups fared worse; significant differences were noted in LARS and some bowel symptoms scores. Conclusion: Bowel function appears better after LE alone compared with treatment strategies involving RT, and composite treatments have an additive effect on outcome impairment. Overall quality of life outcomes are good, despite the ongoing requirement for surveillance. As these treatments become more common it is important that patients can be better informed before deciding on a management pathway.